Basosquamous carcinoma in lower eyelid: reconstruction with auricular cartilage graft associated with the Tripier flap after Mohs surgery - Leonardo Mello Ferreira; Frederico Hassin Sanchez; Pamella Paola Bezerra de Oliveira (Sociedade Brasileira de Dermatologia (SBD), 2020)
Basosquamous carcinoma has a high potential for local recurrence and metastasis, especially when it recurs and at the periocular area. A 49-year-old man underwent Mohs micrographic surgery and subtotal reconstruction of the lower eyelid with cartilage graft from the helix of the ear associated with the Tripier flap, evolving with excellent functional and aesthetic results.